ВИЗНАЧЕННЯ СТРАТЕГІЧНОЇ ПОВЕДІІНКИ ПІДПРИЄМСТВ ЩОДО ВПРОВАДЖЕННЯ НИМИ СОЦІАЛЬНО ВІДПОВІДАЛЬНИХ ПРАКТИК - Краснокутська, Н. С.; Гао, Л. (Підприємництво і торгівля, 2023)
The article provides scientific and methodological provisions for determining the strategic behaviour of an enterprise to implement socially responsible practices, compliance with which ensures the objectivity of management decisions in the field of their socially responsible activities. In order to determine the strategic behaviour of an enterprise in terms of implementation of socially responsible practices, a scientific and methodological approach is substantiated, based on the analysis of the gap between the level of implementation of the Sustainable Development Goals (SDGs) by an enterprise and the activity of these processes at the industry level. To identify the implementation of the SDGs at enterprises, the implementation rate was used, calculated on the basis of a set of single indicators using the binary assessment method for organisational support, systematic implementation and the complexity of the results of socially responsible programmes and projects. For defining the activity of implementation of the principles of sustainable development in the practice of enterprises, the article proposes to use an integral indicator calculated on the basis of comparison of the rate of change of single indicators of costs related to socially responsible practices for enterprises of a particular industry and enterprises of the economy as a whole. For the purpose of definition of the enterprise’s strategic position with regard to implementation of the principles of social responsibility, a two-dimensional matrix with 5×5 parameters was developed, built using complex indicators of implementation of the SDGs and activity of their implementation. Depending on the position held by the enterprise in the matrix "implementation of the SDGs - activity of implementation of the principles of sustainable development by enterprises in the industry", recommendations on the strategic behaviour of the enterprise in the field of implementation of socially responsible practices have been developed. The use of the developed scientific and methodological approach based on the data of enterprises operating in the food production sector allowed to offer recommendations on their optimal behaviour in the development of socially responsible programmes and projects.